Carfilzomib 56 mg/m2 twice-weekly in combination with dexamethasone and daratumumab (KdD) versus daratumumab in combination with bortezomib and dexamethasone (DVd): a matching-adjusted indirect treatment comparison. Issue 8 (3rd July 2022) - Weisel, Katja; Nooka, Ajay K.; Terpos, Evangelos; Spencer, Andrew; Goldschmidt, Hartmut; Dirnberger, Franziska; DeCosta, Lucy; Yusuf, Akeem; Kumar, Shaji
Abstract: Given the increasing use of frontline lenalidomide-based therapies in multiple myeloma (MM), there is an emerging need for lenalidomide-sparing regimens at relapse. Carfilzomib plus dexamethasone and daratumumab (KdD) and daratumumab plus bortezomib and dexamethasone (DVd) are lenalidomide-sparing triplet regimens that are approved for relapsed and/or refractory MM (R/RMM). In the absence of a head-to-head trial comparing these treatments, a matching-adjusted indirect treatment comparison (MAIC) was conducted to assess the efficacy and safety of KdD versus DVd. Results showed that treatment with KdD decreases the risk of progression or death versus DVd (HR 0.64; 95% confidence interval (CI): 0.46–0.90). Time-dependent analysis demonstrated a larger benefit for KdD after the first eight cycles. Unmatched subgroup analysis indicated that KdD may be particularly effective in lenalidomide-exposed and -refractory patients. The present analysis suggests that KdD improves outcomes compared with DVd in patients with R/RMM and may provide a rationale for a preferential treatment.